Accurately measurement and efficiently recovery of ionic liquid in energy utilization of microalgae. (February 2019) - Lu, Haitao; Yu, Xinhai; Li, Hailong; Schwede, Sebastian; Tu, Shan-Tung
Abstract: Chlorella vulgais, a kind of micro-alagae, is an attracting feedstock for bioenergy production, such as biodiesel and biogas. But its tough cell wall structure is the main obstacle to efficiently extracting lipids and other biomass. Ionic liquid (IL) can be used to hydrolyze its cell-wall. However, due to its high cost and toxicity, it is important to recover IL as much as possible. Therefore, a method that can accurately measure the content of ILs, is urgently needed. In this work, two common methods that are used to measure the content of ILs: equimolar titration method and ultraviolet absorbance spectra were compared. The results show that equimolar titration method is not available for trace quantity analysis of ionic liquids as the endpoint of titration is hard to be identified at low IL content (<10 mg/L); while UV absorbance spectra method can be used at low IL contents, whereas, it may result in big deviations. To further improve the accuracy of UV absorbance spectra method, concentrating the sample could be a potential solution.